2007
DOI: 10.1073/pnas.0704000104
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of host cellular multivesicular body functions in hepatitis B virus budding

Abstract: Hepatitis B virus (HBV) is a major human pathogen that chronically infects Ϸ350 million people, causing liver disease and liver cancer. HBV virions bud into an endoplasmic reticulum (ER)-associated intracellular compartment, but the mechanisms of HBV assembly, budding, and release remain poorly understood. Budding of retroviruses and some other enveloped RNA viruses from plasma membranes requires host functions involved in protein sorting into late endosomal multivesicular bodies (MVBs). To determine whether b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
251
0
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 238 publications
(263 citation statements)
references
References 63 publications
9
251
0
3
Order By: Relevance
“…Nevertheless, results from this work showed that Dane's-like particles and SVP localize in different cellular compartments. This is in agreement with recent evidences showing that the viral and subviral HBV assembly pathways seemingly differ in their requirement for cell functions and trafficking routes [25,26] . While HBV virions budding required the involvement of MVB functions, the mechanisms of SVP production showed to be clearly distinct and likely independent of MVB functions [25,26] .…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Nevertheless, results from this work showed that Dane's-like particles and SVP localize in different cellular compartments. This is in agreement with recent evidences showing that the viral and subviral HBV assembly pathways seemingly differ in their requirement for cell functions and trafficking routes [25,26] . While HBV virions budding required the involvement of MVB functions, the mechanisms of SVP production showed to be clearly distinct and likely independent of MVB functions [25,26] .…”
Section: Discussionsupporting
confidence: 81%
“…Most of these viruses access the MVB machinery through its virusencoded late assembly domains and bud through the plasma membrane. In addition, recent communications have reported the involvement of MVB functions in HBV virion maturation and egress using virusreplicating liver cell lines [25,26] . HBV virions have been suggested to bud into internal MVB-related compartments and exit the cell by the exosome pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the findings of others, HBV appears to utilize the MVB (Kian Chua et al, 2006;Lambert et al, 2007;Watanabe et al, 2007) and autophagic compartments (Li et al, 2011;Sir et al, 2010;Tian et al, 2011) during assembly, maturation and release. As Rab7 is known to regulate the dynamics and traffic between these late endocytic compartments and the lysosome (Cantalupo et al, 2001;Jäger et al, 2004;Stenmark, 2009), we tested whether alterations in Rab7 expression and/or function might interfere with the viral life cycle.…”
Section: Hbv Resides Within Markedly Tubulated Rab7-associated Mvb Comentioning
confidence: 99%
“…Recently, a compartment of the late endocytic pathway, the multivesicular body (MVB), has been shown to participate in the final stages of HBV maturation and release. The HBV appears to reside transiently in the MVB and disruption of this compartment results in a decrease of released HBV (Kian Chua et al, 2006;Lambert et al, 2007;Stieler and Prange, 2014;Watanabe et al, 2007). Although the structural interactions between the HBV and this organelle remain unclear, it appears that virus buds inwards into invaginations of the MVB limiting membrane, forming intraluminal vesicles (ILVs), a process that is topologically equivalent to enveloped viral budding from the cell surface (Prange, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Positive-sense strand synthesis by viral polymerase and pregenomic mRNA degradation by a ribonuclease follows. The encapsidated viral genome may now be enveloped by a lipid envelope containing embedded HBsAg and be secreted from the host hepatocyte [47][48][49].…”
Section: Viral Life Cyclementioning
confidence: 99%